Love as Seeing in Truth: Sartre and Stein on Self-Constitution - Cloutier, Chase (Lumen et Vita, 2018)
Realizing who I am and who I am called to be depends in part on my relation to others. Others empathizing with me significantly impacts my self-understanding and character formation. The possibility of a positive encounter is vital because of its role in self-constitution. Both Jean-Paul Sartre and Edith Stein recognized the great import of the gaze of another in the realization of one's own personhood and personal development. However, due to different appraisals of the meaning of human life, Stein evaluates the ultimate import of intersubjective experience as positive whereas Sartre deems it negative. Sartre characterizes interpersonal relations as necessarily combative and conflictual: in order to realize one's full stature and freedom, one must objectify the other so as to escape the other's dominating look. For Sartre the only look one can receive is a look of hatred which attacks and steals one's dignity. On the other hand, Stein proposes that the look of the other has the power to reveal the true and full potential of the self, even counteracting false self-appraisal. A look or attitude of love from another can reveal one's capacity for virtue and initiate one along this path of virtue. In order to overcome the wounds of cultural commodification of the person, we must approach one another in love. Though Sartre offers a particularly incisive diagnosis of “fallen” intersubjectivity and interpersonal relations of objectification, Stein's thought can work to correct and complete his insights on the look of the other, offering a basis for understanding “redeemed” interpersonal relationships in a civilization of love.